FILOSOFIS PRINSIP DASAR MANAJEMEN PENDIDIKAN ISLAM - Komairatul Fitria, Nur Laili; Hamidah, Tutik (CV. Adiba Aisha Amira, 2024)
The basic principles of Islamic Education Management contain various flexible general principles so that they are well in line with the progress and developments of the current era. These principles are what differentiates educational management in general from Islamic educational management. Regarding the principles of Islamic education management, many Islamic education experts have different opinions. Therefore, in this digital era, namely the Industrial Revolution Era 4.0, there is a need to revitalize studies regarding the principles of Islamic education management in order to realize strong and superior management. This type of research is qualitative research in library research. The approach uses a qualitative approach. The findings in this research are that the basic principles in Islamic education management and their relevance in life in the Era of Industrial Revolution 4.0 include the principles of sincerity, honesty, trust and fairness.